2013
DOI: 10.1177/0957650912468408
|View full text |Cite
|
Sign up to set email alerts
|

Applications of optimal building energy system selection and operation

Abstract: Berkeley Lab has been developing the Distributed Energy Resources Customer Adoption Model (DER-CAM) for several years. Given load curves for energy services requirements in a building microgrid (µ⋅grid), fuel costs and other economic inputs, and a menu of available technologies, DER-CAM finds the optimum equipment fleet and its optimum operating schedule using a mixed integer linear programming approach. This capability is being applied using a software as a service (SaaS) model. Optimisation problems are set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As previous DER-CAM investigations have shown the tariff structure and in particular the rates imposed on power demands have a strong influence on the optimal behavior and configuration of DER installations [21][22][23] Tariffs with high on-peak energy rates and on-peak demand charges create opportunities for economic savings from load shifting. An investigation of a large religious building in Saudi Arabia found that the absence of tariff demand charges significantly reduced the economic feasibility of chilled water TES systems, despite a large disparity between on-peak and off-peak cooling consumption [24].…”
Section: Electricity Tariffmentioning
confidence: 99%
“…As previous DER-CAM investigations have shown the tariff structure and in particular the rates imposed on power demands have a strong influence on the optimal behavior and configuration of DER installations [21][22][23] Tariffs with high on-peak energy rates and on-peak demand charges create opportunities for economic savings from load shifting. An investigation of a large religious building in Saudi Arabia found that the absence of tariff demand charges significantly reduced the economic feasibility of chilled water TES systems, despite a large disparity between on-peak and off-peak cooling consumption [24].…”
Section: Electricity Tariffmentioning
confidence: 99%
“…DER-CAM has been in development by Lawrence Berkeley National Lab (LBNL) for over 10 years, and has been widely used to assess DER alternatives, to find optimal results, and for energy-economic assessments [6,7,8]. Figure 2 shows the energy flows modeled by DER-CAM.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 12 illustrates the commercial building energy cost optimization results and their CO 2 abatement potential, expressed in terms of energy and emissions intensity. For each city, there is a baseline "Do-Nothing" case, which reflects an existing situation where electricity and natural gas are purchased from the local utilities, and buildings use electric chillers for cooling 7 Due to absence of more detailed data, this study assumes a static macrogrid marginal CO 2 emissions factor, which represents a fair approximation to reality. Marginal emissions from the grid vary slightly during the different seasons of the year and between day and night hours.…”
Section: Technologies Cost and Performancementioning
confidence: 99%
“…As an example, the Santa Rita Jail of Alameda County, CA, has a peak electricity demand of around 3 MW and a capacity of 4,500 inmates. (49) The facility has a 1.2 MW PV system in addition to a relatively large (1-2 MW) battery installed onsite. Some correctional facilities such as the Worcester County Jail in Massachusetts are implementing small-scale wind generation to meet the energy demands of the facility as well as to provide power to neighboring loads by selling electricity back to the grid.…”
Section: Costs Not In the Modelmentioning
confidence: 99%